Reassessing UslÅ«b IstifhÄm in MukhtÄr al-Aá¸¥ÄdÄ«á¹¡ an-Nabawiyyah: Implications for Artificial Intelligence Interpretation - Nurahman Majid,; Muhamad Nurhasan,; R Edi Komarudin, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the relationship between syntactic structure and rhetorical meaning in uslÅ«b istifhÄm within MukhtÄr al-Aá¸¥ÄdÄ«á¹¡ an-Nabawiyyah by integrating naá¸¥w and 'ilm al-ma'ÄnÄ«. Previous studies have primarily focused on identifying interrogative particles or classifying rhetorical meanings, while the interaction between syntactic structure and contextual meaning remains underexplored. Employing a qualitative library research design, this study analyzes 45 interrogative expressions identified from 183 hadiths in KhÄtimÄtun fÄ« Taá¸hÄ«b an-NufÅ«s. Data were collected through documentation and analyzed using syntactic and rhetorical approaches. The findings reveal that interrogative constructions function predominantly as istifhÄm ghair á¸¥aqÄ«qÄ«, expressing rhetorical meanings such as at-tashwÄ«q, at-taqrÄ«r, al-amr, al-inkÄr, at-ta'ajjub, at-ta'áº“Ä«m, and at-tanbÄ«h 'alÄ á¸alÄl. These meanings are determined not solely by grammatical structure or interrogative particles but through the interaction between syntax, siyÄq al-kalÄm, qarÄ«nah, and communicative purpose. This study proposes an integrated analytical framework that enriches Arabic linguistic studies and provides a conceptual foundation for context-sensitive AI-assisted hadith interpretation.